Gut Microbiota and Paediatric Endocrine-metabolic Disease: A Critical Appraisal of the Evidence in Childhood Obesity, Type 1 Diabetes, Steatotic Liver Disease and Growth Disorders - Ashraf Soliman; Fawzia Alyafei; Nada Alaaraj; Shayma Elsayed; Noor Hamed; Shayma Ahmed; Moataz Derbala (Journal of Advances in Medicine and Medical Research, 2026)
The intestinal microbial community assembles during the same developmental window in which adiposity, islet autoimmunity, hepatic lipid handling and linear growth are established, and this temporal coincidence has encouraged the view that microbial variation is a modifiable determinant of paediatric endocrine-metabolic disease. Evidence supporting that view is unevenly distributed across disorders and rests on designs of very different inferential strength. This critical narrative review evaluates the state of knowledge across four domains that are usually reviewed separately: childhood obesity and adiposity, type 1 diabetes and islet autoimmunity, paediatric metabolic dysfunction-associated steatotic liver disease, and disorders of linear growth including undernutrition-associated growth faltering. Literature was identified through structured searching of biomedical and multidisciplinary scholarly indexes, supplemented by citation tracking and by a regional index, and appraised for design adequacy, confounder control, analytical robustness and replication rather than for citation count. The synthesis indicates that mechanistic and gnotobiotic work provides reasonably strong support for microbial contributions to energy harvest, mucosal immune calibration, gut barrier function, bile acid signalling and somatotropic axis activity, whereas human paediatric evidence is dominated by cross-sectional case-control comparisons with modest samples, inconsistent taxonomic findings and limited adjustment for diet, adiposity, medication and geography. The strongest causal human evidence is found where interventions were designed against a defined microbial target, most notably microbiota-directed complementary feeding in undernutrition; the weakest is in obesity, where taxonomic signatures replicate poorly and intervention effects on adiposity are small and short-lived. Consistent shortcomings include reliance on faecal amplicon profiling as a proxy for a functionally heterogeneous ecosystem, scarce longitudinal sampling through puberty, and near-absence of hard clinical endpoints. Priorities include strain-resolved longitudinal cohorts spanning pubertal transition, target-engagement trials with prespecified microbial mediators, and deliberate representation of populations in which growth faltering and obesity coexist.